Association of Lactate Levels and Mortality in Intensive Care Units - Ardi Pramono; Dey Salwa Aristya Nur; Nadhifah Atsani; Basuki Rahmat; Hadhimulya Asmara (Syntax Idea)
Most critically ill patients experience hemodynamic disorders that cause a decrease in blood perfusion, resulting in hypoxia that can increase lactate production. This study will examine the relationship between lactate levels and mortality in intensive care. This study uses a quantitative observational analytical method with a cross-sectional study design and using medical record data. Data analysis was carried out using an Independent T-test to see if there was a significant difference between lactate levels in the blood of dead and living subjects. This study, 154 subjects were obtained, consisting of 96 males (62.3%) and 58 females (37.7%). The average lactate level in the death group was 3.99, and the live group was 2.4 (p=0.004). Subjects with higher lactate levels have higher mortality rates. Lactate levels are one of the indicators of tissue oxygenation in critically ill patients. Hyperlactatemia is common in critically ill patients and can reflect an imbalance between local or systemic oxygen delivery and demand. Hyperlactatemia can cause lactic acidosis or metabolic acidosis and is associated with high mortality outcomes. Increased lactate levels are also associated with the development of Multiple Organ Dysfunction Syndrome (MODS). Subjects with high lactate levels are often associated with a variety of etiologies and poor prognosis, especially critical patients in the Intensive Care Unit (ICU). There was a relationship between blood lactate levels and mortality in ICU patients.